PERAN PEKERJA SOSIAL DALAM PENYEMBUHAN TRAUMATIK UNTUK KEBERLANGSUNGAN HIDUP KORBAN; Studi Kasus Pada Korban Kehamilan Tidak Diinginkan di Balai Perlindungan dan Rehabilitasi Sosial Wanita Yogyakarta - Nerisa Afwan (UIN Sunan Kalijaga Yogyakarta, 2019)
This study discusses how the role of social workers in healing traumatic victims of KTD (Unwanted Pregnancy). The purpose of this research is to find out what are the roles played by social workers in healing traumatic victims of KTD. This study uses qualitative research through observation and interview techniques in which researchers are directly involved in the research process to obtain the information needed. The subject of the informants in this study were social workers who handled the victims of unwanted pregnancies in Women's Social Protection and Rehabilitation Center (BPRSW). The results of this study indicate that the role of social workers in healing traumatic victims of KTD is done by providing guidance, motivation and advice to victims so that victims are free from trauma and can continue their lives well in pregnancy.Keywords: The Role Of Social Workers, Healing Of Traumatic, Unwanted Pregnancy